Characterisation of Sicilian Cheese made from the milk of Sicilo-Sarde breed ewes in the North West of Tunisia - Damergi C.; Moujahed N.; Ben Sid Elhaj S.; Kayouli C. (Nutritional and foraging ecology of sheep and goats, 2009)
For about one century, Sicilian Cheese has traditionally been made in the North West of Tunisia, using milk from Sicilo-Sarde breed ewes (SSE). Recently, some small manufacturers started to make it industrially. In the current study we tried to characterize this cheese as produced using the traditional way (TC) or following small scale industrial methods (IC). The study concerned a farmer producing cheese from his own SSE milk and a small manufacturer in the region of Tunis (100 km far from Béja). In each case, milk was characterised chemically. Both processes of cheese making were described. Cheeses obtained were compared on the basis of yield (G), chemical composition, microbiological and sensory attributes. For all measurements three replications were carried out through three successive trials. The milk used in the two processes was chemically comparable. Output in TC was comparable to IC (averaged 30.5). Dry matter and fat were higher in IC, while higher protein contents were observed in TC (P < 0.05). Better hygienic conditions, mainly for coliform and lower microbial contamination, mainly for moulds and yeast were noted in IC (P < 0.001). Sensory analysis revealed significant differences between TC and IC. Indeed, TC has a marked yellow colour (P < 0.05), better taste (P < 0.01) and aromatic intensity (P < 0.01). It was concluded than Sicilian traditionally-made cheese could be identified as a labelled product if some improvements in hygienic practices are applied at different steps of milking and cheese manufacturing. A marketing strategy is needed to ensure the promotion of this cheese.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)